Analiza razlik v dosežkih učencev/dijakov ter analiza primarnih in sekundarnih učinkov družbenih razlik na dosežke učencev/dijakov - Gaber, Slavko (Šolsko polje, 2009)
This secondary study analyses Slovenian students' science performance in the international comparative study PISA 2006 within the context of social reproduction. We were especially interested in comparisons with selected countries (Finland, Estonia, and Norway), and also, in places, comparisons with other countries included in PISA 2006, especially student performance at the OECD average. An analysis of between-school and within-school differences in student performance indicates that the large differences in performance of Slovenian students must be attributed to the various secondary-school programs that Slovenian 15-year-olds were enrolled in when tested. All of the additional calculations that we used to help explain the performance of Slovenian students versus their peers from the countries compared (with predictors included) indicate that the calculations and interpretation of between-school and within-school differences in student performance presented in the PISA 2006 report are not precise enough because they overlook certain important differences between the school systems in different countries. Taking into account the findings presented in the PISA 2006 report, our own calculations, and various concepts of educational system fairness and effectiveness, we determined that the economic, social, and cultural status (ESCS) of students' parents has an important effect on student performance at the primary level. Findings from the analysis of primary and secondary effects of social inequality (student inclusion in various educational programs, student aspirations and motivations in various educational programs,the grades that they 'bring' with themselves, and the role of ESCS in inclusion in various programs despite having identical grades in school) indicate that mechanisms and measures must be created in the Slovenian school system to reduce the effects of social inequality.
Keywords: dijaki; družbena neenakost; družbene razlike; mednarodne raziskave; Slovenija; učenci; učna uspešnost; znanje